THE KARYOTYPES OF POUCHED AMPHISTOMES - REDDY, P. VENKAT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The karyotypes of the three amphistomes, Gastrothylax crumenifer (Creplin, 1847) Poirier, 1883, Fischoederius Cobboldi (Poirier, 1883) Stiles and Goldberger, 1910 and Fischoederius elongates (Poirier, 1883) Stiles and Goldberger, 1910 from ruminants were studied using the squash and flame drying techniques. Except F. elongates (2n = 16) other two species demonstrate 2n = 18 chromosomes. Meiotic configurations were also studied to substantiate chromosome numbers. The results are discussed in terms of evolutionary relationship of morphologically well defined amphistomes.